Online repository system for Petakom club - Irzad, Hairani (2012)
This thesis presents the development of a web-based system customized to serve the need of a PETAKOM club of FSKKP in UMP.The system is designed to replace a paper-based process that gradually become unmanageable due to the increasing large volume of data.Features of the new system include online recording of forms,database query functions, activities update,members update,manage and monitor the progress data and activities included in Petakom.The design principles and introduce a functional component diagram for the system.The system is implemented on Windows platform using open source software such as PHP,MySQL,and Apache. Performance of the developed system is assessed practically and an efficient,and user friendly operation is demonstrated.